தமிழ்ப் படிநிலைத் தேர்வுத்தாள் கோவை (தொடக்க நிலை) - (:unkn) unknown (Central Institute of Indian Languages Mysore, 2010)
The book gives a collection of graded test modules for regulating the process of test construction and item preparation in language education for primary level.
Compendium of Graded Tests in Tamil (Primary)
Keywords: Tamil; Compendium of Graded Tests in Tamil (Primary); Language Learning; Tamil; Tamil